Dynamics of aerobic capacity and force-velocity characteristics of arm and leg muscles in junior cross-country skiers - Butkov, A.; Lysenko, E.; Lemesheva, Y.; Popov, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The goal of our study was to evaluate dynamics of aerobic capacity and force-velocity characteristics of arm and leg muscles in junior cross-country skiers during on-snow training season. Six junior subnational level cross-country skiers (19.3±1.1 years old, VO2max 63.3±5.9 ml/min/kg) participated in 4 physiological test sessions from November to March. Maximal anaerobic power (MAnP) of arm muscles was determined in a 10-second maximal effort test by double poling ergometer. Maximal torques of knee extensor muscles at various angular velocities (30 degrees/s - 300 degrees/s) were measured by isokinetic dynamometer. Aerobic capacity [maximal oxygen consumption rate (VO2max) and V`O2 at blood lactate level (La) 4 mmol/l] was evaluated in incremental tests using double poling ergometer and running treadmill. In the beginning and in the end of the test period volume of m. quadriceps femoris and m. triceps brachii as well as body composition were evaluated by magnetic resonance imaging and anthropometry, accordingly. No MAnP increase was found during training period. Knee extensors torque did not change at low angular velocity (30 degrees/s), whereas a decrease (7.8%, P<0.05) was found at 300 degrees/s. Initial VO2max in double polling and treadmill tests were 3.7±0.6 and 4.5±0.6 l/min, accordingly, and did not change during the training period. VO2 at La 4 mmol/l in treadmill test was 3.6±0.8 l/min and also did not change. However, VO2 at La 4 mmol/l in double polling test gradually rose during the testing period from 2.2±0.8 to 2.8±0.7 l/min. Increase of aerobic capacity in incremental double poling test can be explained by initially very low level of aerobic capacity: VO2 at La 4 mmol/l was lower compared with that in treadmill test - 2.2±0.8 and 3.6±0.8 l/min, accordingly. That difference may be associated with low arm muscles training volume over preparation period compared to leg muscles. High volume of leg muscle aerobic training may have negative effect on leg muscle strength and cross-section area.